Allium spp. as a Source of Bioactive Antibacterials: A Review of Compounds, Mechanisms, and Effectiveness - Hasibuan, Febry Rahmadhani; Pujiyanti, Aloysia Sri; Ilmi, Annisa Nurul; Hariani, Nova (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Allium spp. has long been recognized for its diverse therapeutic benefits, particularly as a natural source of antibacterial agents. Various bioactive compounds found in Allium spp., such as allicin, diallyl disulfide, ajoene, and quercetin, have demonstrated significant antimicrobial activity against both gram-positive and gram-negative bacterial pathogens. Research on the mechanisms of antibacterial action of these compounds reveals that they work by disrupting bacterial cell membranes, inhibiting protein synthesis, and interfering with bacterial metabolism. This literature review aims to examine existing studies on the antibacterial potential of Allium spp., reviewing the bioactive compounds involved, their mechanisms of action, and their effectiveness in inhibiting bacterial growth, including antibiotic-resistant pathogens such as methicillin- resistant Staphylococcus aureus (MRSA) and Escherichia coli. The findings of this review indicate that while their effectiveness may vary depending on the specific compound and form of application, Allium spp. shows considerable promise as a natural alternative for combating bacterial infections and addressing the growing issue of antibiotic resistance. This article provides deeper insights into the relevance and potential of Allium spp. in the development of antimicrobial therapies based on natural sources through a literature-based approach.